2020
DOI: 10.1101/2020.11.27.400879
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial Suitability Modeling of Zoonosis: Implicated Risk Areas of B. anthracis and Trends under climate change Scenarios in Ethiopia

Abstract: The causative agent of Anthrax B. anthracis has long been known to cause disease in animals and humans. Its worldwide distribution includes Ethiopia as an endemic country to the disease. The current study was aimed at identifying and developing risk maps, in areas that are suitable for the persistence of anthrax spores under climate change scenarios by using anthrax occurrence data and other predictor variables in MaxEnt model. A total of 158 occurrence locations were used as inputs along 10 current bioclimati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In addition, animals that graze short grasses close to the ground during the dry season are more likely to be exposed to spores thereby increasing the possibility of anthrax outbreaks. The dry season also results in water and forage shortages leading to a higher anthrax transmission in livestock and wildlife at remaining water points [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, animals that graze short grasses close to the ground during the dry season are more likely to be exposed to spores thereby increasing the possibility of anthrax outbreaks. The dry season also results in water and forage shortages leading to a higher anthrax transmission in livestock and wildlife at remaining water points [6].…”
Section: Discussionmentioning
confidence: 99%
“…Although the disease burden of anthrax in herbivores is not fully known, studies have shown that anthrax outbreaks occur almost every year killing thousands of animals and transmitting the disease to humans upon consumption of the meat [1]. The disease is of global concern as it results in high animal mortality with subsequent threats to human health [5,6]. Despite a decrease in reported livestock anthrax cases globally in the past decade [7] between 20,000 to 100,000 cases of the disease are still being recorded each year especially in developing countries [4].…”
Section: Introductionmentioning
confidence: 99%
“…The highest number of animal deaths due to anthrax were reported in Banja district (n = 68) followed by Zigem district (n = 57), while the lowest number of animal deaths was recorded in Fagita Lekoma district. Differences in the number of anthrax cases and deaths among districts might be due to varying climatic, soil, and temperature conditions 19 , 26 as well as carcass and environmental management practices following animal anthrax cases and deaths, 9 , 14 which will facilitate the clustering of anthrax in a specific place. 6 Although B. anthracis can be found worldwide, anthrax cases usually occur only in limited geographic regions.…”
Section: Discussionmentioning
confidence: 99%